MENAKAR PROGRESIVITAS TEKNOLOGI FINANSIAL (FINTECH) DALAM HUKUM BISNIS DI INDONESIA - Mariske Myeke Tampi (Faculty of Law - Tarumanagara University, 2019)
The PBI Number 19/12/PBI/2017 concerning the Implementation of Financial Technology is a staple of policy that shows the Financial Technology (Fintech) has been allowed to exist in Business Law in Indonesia such as business to business and business to consumer with particular limitation. The regulation on electronic money that has been enacted before the issuance of PBI Number 19/12/PBI/2017 is also included in the definition of Financial Technology (Fintech) in PBI Number 19/12/PBI/2017. Enormous benefits from Financial Technology (Fintech) is a driving force of the progressivity of the Financial Technology (Fintech) regulation. Review of laws relating to Financial Technology (Fintech) in Indonesia illustrates that the policy of Financial Technology (Fintech) is quite progressive. Such progressivity may be examined from the view point of Satjipto Rahardjo’s progressive law theory and Roscoe Pound’s sociological jurisprudence. The cause of the emergence of rules regarding current Financial Technology (ius constitutum) is contained in 4 points of urgency and 3 (three) points of consideration of Bank Indonesia Regulation Number 19/12/ PBI/2017. As long as the product of Financial Technology does not conflict with the existing value system, the Financial Technology product can be developed and regulated in Indonesia in the future (ius constituendum).